Strain Prediction of Grain in Solid Rocket Motor under the Pressure Curing Molding Technology - Kaining Zhang; Chunguang Wang; Qun Li; Zhenyu Guo (International Journal of Aerospace Engineering)
The residual strain generated in grains during the propellant manufacturing process can significantly impact the safety and stability of solid rocket motors. Pressure curing molding technology has been employed as an effective approach to mitigate residual strain. This research paper focuses on deriving a strain prediction function for grains based on continuum mechanics, taking into account the influence of pressure curing molding technology. The accuracy of the prediction function is verified through finite element analysis. The results show that the proposed function accurately predicts strain distribution at critical positions within the grains. And the effects of curing pressure and the elastic modulus of the case on residual strain are analysed. Specifically, for a given material of case, an optimal curing pressure is identified that minimizes residual strain in the grains. Moreover, it is observed that materials with lower hoop elastic modulus, such as composites, tend to require lower optimal curing pressures. The outcomes of this study provide valuable guidance for grain shape design and the selection of optimal curing pressure.